Piezoelectric energy harvesting system via impact and vibration – A review - Basari, Amat Amir; Ng, Xue Yan; Kok, Swee Leong; Ahmad Nawir, Nur Amalina (Penerbit Universiti, UTeM, 2019)
Recently, the vibrational energy harvesting devices have been studied and developed significantly. Although battery is the main power source for electronic devices, it still has some limitations, particularly its life time. Piezoelectric transducer is one of the devices that can be used for the vibration energy harvesting system. It has higher power density compared to the others. A comprehensive review on piezoelectric energy harvesting system is discussed and presented in this paper. The techniques of the piezoelectric energy harvester such as impact and vibration modes are reviewed. The power generator developed for the impact-based piezoelectric energy harvester is addressed in this paper. It can be concluded that the piezoelectric energy harvesting system can generate output power in the range of 34.6nW to 1.34W.